Ethnocracy and Multiculturalism: A Preliminary Study of The Cultural Aspects of The Besemah People At Pagaralam, Palembang - Meliono, Irmayanti (Makara Human Behavior Studies in Asia, 2011)
This paper aims to show that the traditional governance system, Lampik Empat Merdike and Sindang merdike (free men) established by the Besemah society in the past is the source of enthusiasm and democratic spirit in Besemah ethnocratic society. Besemah people's lives have changed through many different periods, from the megalithic, to the imperial, the colonial and to post-colonial (independence) periods. The kind of change that has taken place is concerned with the society’s view of diversity in various aspects, such as culture, knowledge, the world outside the ethnic community of Besemah, and education. Thus, multiculturalism is a unique characteristic of the Besemah community. There are two important aspects of multiculturalism in the Besemah community, namely: (1) interaction and communication between different cultures (Besemah and Dutch), (2) changes in public perception regarding the Besemah from local to global perceptions. These demonstrate that the community has a unique type of multiculturalism based on ethnocracy and the traditional governance system.The research shows that multiculturalism in Besemah society still exists in their daily lives and has a pragmatic function to improve the quality of life in various sectors.